Indications and foeto-maternal outcome of emergency cesarean sections in rural Mewar region - Verma, Savitri; Bamniya, Archana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: In the 21st century caesarean section is the most common operation in modern obstetrics but its indications have been changed in elective and emergency cases. The aim of the present study was to find out the incidence, indication of caesarean, foeto-maternal outcome in patients who came in emergency from rural areas. Methods: This retrospective study was conducted at Pannadhai Mahila Hospital, R. N. T. Medical College, Udaipur from September 2017 to February 2018. All the women who were unbooked, belonged to rural Mewar region and underwent emergency caesarean section. Results: Total no. of deliveries conducted were 1560 in the emergency labour room out of which 462 were emergency caesarean sections. The mean age of the participants was 27 years. Foetal distress was the most common indication (17.75%) followed by prolonged labour/ failed induction 14.5%. Post-partum haemorrhage and adhesions were the commonly encountered complications. Conclusions: LSCS due to maternal and foetal indications is inevitable. Timely performed LSCS decreases the morbidity and mortality. The government of India has also taken initiative in making caesarean deliveries more acceptable, affordable to patients belonging to rural areas. The government is also enhancing primary and community health centers.